2017
DOI: 10.3390/polym9040120
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biomimetic Approach to Repair Enamel Cracks/Carious Damages and to Reseal Dentinal Tubules by Amorphous Polyphosphate

Abstract: Based on natural principles, we developed a novel toothpaste, containing morphogenetically active amorphous calcium polyphosphate (polyP) microparticles which are enriched with retinyl acetate ("a-polyP/RA-MP"). The spherical microparticles (average size, 550 ± 120 nm), prepared by co-precipitating soluble Na-polyP with calcium chloride and supplemented with retinyl acetate, were incorporated into a base toothpaste at a final concentration of 1% or 10%. The "a-polyP/RA-MP" ingredient significantly enhanced the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Moreover, it is interesting to point out that previous studies have demonstrated the presence of particles in solutions comprised of PolyPs and cationic species (e.g., Mg 2+ ions). Similar types of particulates containing PolyPs and inorganic divalent cations have also been observed in nature, such as granules in mitochondria, while synthetic analogues can be prepared in alkaline solutions with excess cations for use in applications of bone regeneration and cartilage repair, among others.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, it is interesting to point out that previous studies have demonstrated the presence of particles in solutions comprised of PolyPs and cationic species (e.g., Mg 2+ ions). Similar types of particulates containing PolyPs and inorganic divalent cations have also been observed in nature, such as granules in mitochondria, while synthetic analogues can be prepared in alkaline solutions with excess cations for use in applications of bone regeneration and cartilage repair, among others.…”
Section: Resultsmentioning
confidence: 93%
“…(21,22) Repair of demineralized collagen fibrils by mineral implementation within the gaps between the collagen fibrils was tried by the application of topical remineralizing agents such as casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) known as MI paste plus TM (16,(23)(24)(25)(26) CPP-ACPF is a remineralizing agent derived from the milk and can promote high degree of remineralization in enamel as well as dentin compared to fluoride gel or fluoride tooth paste. (27) It has a great potential to modulate bioavailability of Ca and P levels by stabilization of ionic super saturation of Ca and P to enhance the remineralization process and can bind to positively and negatively charged ions. (28) ACP is the controller of the precipitation of CPP.…”
Section: Introductionmentioning
confidence: 99%
“…This sealant consists of biomimetic amorphous polyP microparticles that can be applied as bioactive ingredient of a toothpaste, mouth rinse, chewing gum or other oral care product. The polyP particles do not only efficiently close enamel/dentin cracks and fissures and carious cavities, but even induce re-mineralization in the treated enamel and dentin, as demonstrated recently by electron microscopy and synchrotron-based x-ray tomography microscopy (SRXTM) (Ackermann et al 2019) and show antimicrobial activity against the cariogenic bacterium Streptococcus mutans (Müller et al 2016b(Müller et al , 2017a(Müller et al , 2017c. This toothpaste repairs enamel defects after short-term treatment and reseals open dentinal tubules, which lead to hypersensitivity of the teeth.…”
Section: Dental Sealantmentioning
confidence: 77%